Development of a mouse monoclonal antibody against the chondroitin sulfate-protein linkage region derived from shark cartilage - Akatsu C. (2014)
Glycosaminoglycans (GAGs) like chondroitin sulfate (CS) and heparan sulfate (HS) are synthesized on the tetrasaccharide linkage region, GlcAβ1-3Galβ1-3Galβ1-4Xylβ1-O-Ser, of proteoglycans. The Xyl can be modified by 2-O-phosphate in both CS and HS, whereas the Gal residues can be sulfated at C-4 and/or C-6 in CS but not in HS. To study the roles of these modifications, monoclonal antibodies were developed against linkage glycopeptides of shark cartilage CS proteoglycans, and one was characterized in detail. This antibody bound hexaand pentasaccharide-peptides more strongly than unsaturated tetrasaccharide-peptides with the unnatural fourth sugar residue (unsaturated hexuronic acid), suggesting the importance of the fifth and/or fourth saccharide residue GalNAc-5 and/or GlcA-4. Its reactivity was not affected by treatment with chondro-4-sulfatase or alkaline phosphatase, suggesting that 4-O-sulfate on the Gal residues and 2-Ophosphate on the Xyl residue were not recognized. Treatment with weak alkali to cleave the Xyl-Ser linkage completely abolished the binding activity, suggesting the importance of the peptide moiety of the hexasaccharidepeptide for the binding. Based on the amino acid composition and matrix-assisted laser desorption ionization time-of-flight mass spectrometry analyses, it was revealed that the peptide moiety is composed of four amino acids, Ser, Pro, Gly, and Glu. Furthermore, the antibody stained wild-type CHO cells significantly, but much weakly mutant cells deficient in xylosyl- or galactosyltransferase-I required for the biosynthesis of the linkage region. These results suggest that the antibody recognizes the structure GalNAc (±6-O-sulfate)-GlcA-Gal-Gal-Xyl-Ser-(Pro, Gly, Glu). The antibody will be a useful tool for investigating the significance of the linkage region in the biosynthesis and/or intracellular transport of different GAG chains especially since such tools to study the linkage region are lacking. © Springer Science+Business Media, LLC 2010.